Robust multi-stage economic dispatch with renewable generation and storage - Yildiran, Ugur (ELSEVIER, 2023)
In this paper, an economic dispatch problem for power grids involving renewable generation and stor-age units is studied. A multi-stage robust optimization algorithm for computing base dispatches and re -dispatches is proposed. Unlike the other approaches in the literature, the proposed method finds an exact solution to the multi-stage robust optimization problem considered when there are no storage devices or storage devices are ideal (i.e. charging/discharging inefficiencies are neglectable). In the presence of non -ideal storage devices, the algorithm can produce upper-bounding approximations. The devised approxi-mation scheme has two distinguishing features. Firstly, the base dispatches and, especially, multi-stage re-dispatch policies computed are guaranteed to be free of simultaneous charges/discharges. Secondly, it produces lower bounds allowing one to assess the quality of solutions. Optimality and convergence properties of the proposed method are proven and it is compared with other alternatives in the liter-ature through numerical experiments. Results show that significant economic benefits can be achieved compared to the other approaches and solutions could be obtained within acceptable time limits for large-scale problems. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: OR In energy; Multi-stage robust optimization; Dynamic programming; Economic dispatch; Energy storage; CONSTRAINED UNIT COMMITMENT; ENERGY-STORAGE; COMPLEMENTARITY CONSTRAINTS; POWER-SYSTEM; WIND POWER; RESERVE DISPATCH; EXACT RELAXATION; TRANSMISSION; OPTIMIZATION; OPERATION; Business & Economics; Operations Research & Management Science